0091 Spindle Characteristics Are Associated With Executive Function In Healthy Older Adults From The Brain In Motion Study. (12th April 2019) - Guadagni, Veronica; Byles, Hannah; Hanly, Patrick J; Younes, Magdy; Poulin, Marc
Abstract: Introduction: Sleep spindles are defining characteristics of NREM stage-2 sleep. Sleep spindle characteristics have been associated with memory consolidation and other cognitive functions, and have been used as marker of progressive cognitive decline in clinical populations. The objective of this study is to further explore the relationship between sleep spindle characteristics and cognitive functioning. Methods: 63 participants (mean age ± SD = 68.02 ±5.67, 30 females) underwent one night of in-home polysomnography (PSG) and cognitive testing in separate sessions. A novel computerized algorithm was used to score PSG data and sleep spindle characteristics were obtained through EEG spectral analysis. A Principal Component Analysis (PCA) was conducted to reduce the number of analyzed cognitive variables and generate factors/domains based on the communalities between the original variables. Stepwise multiple regression analyses were employed to investigate the relationship between spindle characteristics and cognitive measures. All statistics were two-tailed and significance was set at p < 0.05. Results: The PCA generated four factors which explained 76.2 % of the total variance. Factor 1, which explained the largest amount of variance (34.1 %), consisted of outcomes of primary executive functions (processing speed, inhibition and verbal fluency). After controlling for age, the primary executive functions factor was significantly associated with sleep spindle density (β = 0.002, t62 = 2.388, p = 0.020, r 2 = 0.266), duration (β = 0.002, t62 = 2.374, p = 0.021, r 2 = 0.266) and power (β = 0.002, t62 = 2.410, p = 0.019, r 2 = 0.268). No relationship was found between spindle characteristics and the other generated cognitive factors. Conclusion: In our sample of healthy older adults, spindle density, duration and power are associated with executive functions after controlling for the effect of age. This suggests that sleep spindle characteristics may be a potential biomarker of changes in cognitive function in this population. Support (If Any): This work was supported in part by the Canadian Sleep and Circadian Network Multi-site Mentoring Program Award (to VG)